PDZK1 in leukocytes protects against cellular apoptosis and necrotic core development in atherosclerotic plaques in high fat diet fed ldl receptor deficient mice. (September 2018) - Yu, Pei; Qian, Alexander S.; Chathely, Kevin M.; Trigatti, Bernardo L.
Abstract: Background and aims: PDZK1 (Post-synaptic density protein/Drosophila disc-large protein/Zonula occludens protein containing 1) stabilizes the HDL receptor protein, SR-B1, in the liver, and mediates SR-B1 signaling outside of the liver. Complete knockout of pdzk1 increases atherosclerosis in apoE -deficient mice, but the effect of PDZK1 in leukocytes is not known. In this study, we tested the role of leukocyte PDZK1 in atherosclerosis development by using bone marrow transplantation to generate ldlr deficient mice lacking PDZK1 in leukocytes. Methods: Ldlr −/- mice were transplanted with either pdzk1 −/− or pdzk1 +/+ bone marrow and fed a high-fat diet to induce atherosclerosis. Results: Bone marrow specific pdzk1 knockout slightly increased atherosclerotic plaque sizes but strikingly increased sizes of necrotic cores and cellular apoptosis in within plaques. PDZK1 deficiency prevented HDL dependent protection of macrophages from apoptosis in vitro and sensitized peritoneal macrophages to apoptosis in situ . PDZK1 deficiency in macrophages also impaired their ability to engulf apoptotic cells, and attenuated the IL-4 dependent induction of mannose receptor in vitro and mannose receptor protein levels in macrophages in atherosclerotic plaques. Conclusions: PDZK1 is required for anti-atherogenic responses in macrophages including HDL dependent protection against apoptosis and macrophage mediated efferocytosis and limits the accumulation of apoptotic cells within atherosclerotic plaques protecting against necrotic core development. Graphical abstract: Image 1 Highlights: Leukocyte PDZK1 deficiency increases plaque apoptosis and necrotic core formation in high fat diet-fed ldlr knockout mice. PDZK1 deficiency increases sensitivity of macrophages to tunicamycin-induced apoptosis in vivo. HDL protects wild type but not PDZK1 deficient macrophages from apoptosis via a pathway involving Akt1 activation. PDZK1 deficient macrophages also exhibit impaired engulfment of apoptotic cells.